Spin crossover in the Prussian blue analogue FePt(CN)6 induced by pressure or X-ray irradiation. Issue 37 (14th July 2020) - Boström, Hanna L. B.; Cairns, Andrew B.; Liu, Lei; Lazor, Peter; Collings, Ines E.
Abstract : Pressure and X-ray irradiation induced spin crossover is found in Prussian blue analogue FePt(CN)6 . Abstract : The spin state of the Prussian blue analogue Fe II Pt IV (CN)6 is investigated in response to temperature, pressure, and X-ray irradiation. While cooling to 10 K maintains the high-spin state of Fe II, compression at ambient temperature induces a first-order spin-crossover (SCO) transition with a small hysteresis loop ( p ↑ = 0.8 GPa, p ↓ = 0.6 GPa). In addition, the high-spin to low-spin transition can be initiated at lower pressure through increased X-ray irradiation. Our study highlights a cooperative SCO with moderate pressure in a porous Prussian blue analogue.